Confirmation Bias and the Pursuit of Truth in Al-Ghazali’s 'Tahafut al-Falasifah': A Critical Reflection - Masykur, Zein Muchamad; Chasani, Muchamad Toif (Asian Journal of Philosophy and Religion, 2025)
This study examines the influence of confirmation bias in Al-Ghazali's critique of philosophers in Tahafut al-Falasifah. Confirmation bias, a cognitive tendency to seek and interpret information that aligns with pre-existing beliefs, may have influenced Al-Ghazali's critique of Peripatetic philosophy. The analysis focuses on how Al-Ghazali's epistemological framework, emphasizing divine revelation over reason, shaped his argumentation. This paper reveals how confirmation bias plays a role in his selective interpretation of philosophical arguments. Ultimately, the study offers insights into the relationship between theology and philosophy in classical Islamic thought.